1997
DOI: 10.1117/12.281563
|View full text |Cite
|
Sign up to set email alerts
|

<title>Comparative study of the Gaussian form of the Bhattacharyya metric for ATR performance evaluation</title>

Abstract: The Gaussian form of the Bhattachaiyya distance measure is being used by some in the automatic target recognition (ATR) community to select features and to estimate an upper performance bound for ATR algorithms.One reason for the popularity of this measure is that it is readily computed. This paper shows through both empirical and analytic results the inadequacy ofthis metric.Empirical results are obtained by processing ADTS field data through both the Gaussian form of the Bhattacharyya distance and a nonparam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2000
2000
2003
2003

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…A comparative study specifically for ATR performance evaluation [12] found that nonparametric error estimation techniques are superior to those which use the Gaussian form of the Bhattacharyya metric to select features and to estimate upper bounds on ATR performance. To demonstrate this conclusion, Williams used data from the Advanced Detection Technology Sensor (ADTS, 33 GHz, 1-foot resolution) to analyze the distinguishability of grassy and treed areas in SAR imagery.…”
Section: Examples Of the Approachmentioning
confidence: 97%
“…A comparative study specifically for ATR performance evaluation [12] found that nonparametric error estimation techniques are superior to those which use the Gaussian form of the Bhattacharyya metric to select features and to estimate upper bounds on ATR performance. To demonstrate this conclusion, Williams used data from the Advanced Detection Technology Sensor (ADTS, 33 GHz, 1-foot resolution) to analyze the distinguishability of grassy and treed areas in SAR imagery.…”
Section: Examples Of the Approachmentioning
confidence: 97%
“…The approaches include 1. Bayes error-based parametric and nonparametric approaches [15] (use of probability distance measure bounds [7], [45], entropy measures [4], [47], nonparametric estimation including k nearest neighbor [6], [10], [25], [46], and Parzen estimation [28], interclass distance measures [9], [13], [41], [47], probability distances such as Bhattacharya [2], Chernoff [5], etc., for multiclass problems [1], [14]). See [13], [43] for a criticism of such approaches; 2. scatter matrices [7], [13]; 3. information-theory-based approaches [26], [44]; 4. boundary methods [30], [31], [32], [35], [36]; 5. correlation-based approaches [33]; 6. nonparametric methods [17], [20]; and 7. feature space partitioning methods [24].…”
Section: Introductionmentioning
confidence: 99%